An Update on Maternal Use of Antiepileptic Medications in Pregnancy and Neurodevelopment Outcomes - Gerard, Elizabeth E.; Meador, Kimford J. (Journal of Pediatric Genetics, 2015)
Antiepileptic drugs (AEDs) are prescribed commonly to women of childbearing age. In utero exposure to some AEDs can have significant cognitive and behavioral consequences for the unborn child. Recently, prospective studies of women taking AEDs during pregnancy have added significantly to our understanding of cognitive and behavioral teratogenic risks posed by fetal AED exposure. Valproate is clearly associated with impaired cognitive development as well as an increased risk of disorders such as autism and autism spectrum disorder. Exposure to carbamazepine, lamotrigine, levetiracetam, or phenytoin monotherapy is associated with more favorable cognitive and behavioral outcomes than valproate, but more data are required to clarify if these AEDs have more subtle effects on cognition and behavior. There are insufficient data on the developmental effects of other AEDs in humans. Further, the underlying mechanisms of cognitive teratogenesis are poorly understood, including the genetic factors that affect susceptibility to AEDs.
Keywords: epilepsy; pregnancy; mood disorder; antiepileptic; valproic acid; lamotrigine; levetiracetam; neurodevelopment